The performance on concrete brick containing Palm Oil Fuel Ash (POFA) as replacing cement - Mohd Zailani, Tarmidzi; Adnan, Suraya Hani; Abdullah, Mohd Sufyan (Penerbit Uthm, 2018)
Construction field is a field that is wider than the other fields. The construction is becoming increasingly rapidly to meet the growing population. In the field of construction, brick is an essential element to construct a building. Production of concrete leads to a reduction in natural resources as materials used in producing a concrete brick example of fine aggregate and cement. Furthermore, this problem gets attention from some parties in finding an alternative to reduce waste and maintained the natural resources to produce concrete using waste materials. Therefore, waste materials will be used in the concrete mix to reduce landfill and can reduce biomass waste.